THE EFFECTIVENESS OF THE CORRUPTION ERADICATION LAW IN SUPPRESSING CORRUPT PRACTICES IN THE PUBLIC SECTOR - Ansori, Ansori (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the effectiveness of the Corruption Eradication Law in suppressing corrupt practices in the public sector in Indonesia. Corruption in the public sector is one of the biggest challenges in creating clean and accountable governance. The research uses a descriptive-qualitative approach, by collecting data through literature reviews, in-depth interviews with legal experts, and analysis of legal documents and reports of corruption cases handled by related institutions such as the Corruption Eradication Commission (KPK), the Police, and the Attorney General's Office. The research results show that although the Corruption Eradication Law has provided a comprehensive legal framework, its implementation still faces various challenges. The main obstacles include weak coordination between law enforcement agencies, political influence that weakens the independence of institutions such as the Corruption Eradication Committee, and limited application of technology in public sector oversight. In addition, a systemic culture of corruption in various public institutions slows down the expected changes. However, law enforcement efforts supported by the active role of civil society and the media have shown a positive impact in increasing public awareness of the dangers of corruption. Implementing preventive measures, such as strengthening technology-based systems of transparency and accountability and anti-corruption education, is seen as a key element in maximizing the effectiveness of this policy. This research recommends institutional reform, increased legal protection for whistleblowers, and strong political commitment to strengthen efforts to eradicate corruption. With these strategic steps, it is hoped that the Corruption Eradication Law will be more effective in suppressing corrupt practices in the public sector systematically and sustainably.